Effect of different levels of concentrate on ruminal microorganisms and rumen fermentation in Nellore steers - Granja-Salcedo, Yury T. [UNESP]; Ribeiro Junior, Carlos S. [UNESP]; Jesus, Raphael B. de [UNESP]; Gomez-Insuasti, Arturo S. [UNESP]; Rivera, Astrid R.; Messana, Juliana D. [UNESP]; Canesin, Roberta C.; Berchielli, Telma T. [UNESP] (Taylor & Francis Ltd, 2016)
The aim of this study was to investigate the effect of different dietary levels of concentrate on feed intake, digestibility, ruminal fermentation and microbial population in steers. Eight Nellore steers fitted with ruminal cannulas were used in a double 4x4 Latin square design experiment. The dietary treatments consist of four different proportions of concentrate to roughage: 30:70, 40:60, 60:40 and 80:20% in the dry matter, resulting in Diets 30, 40, 60 and 80, respectively. The roughage was corn silage, and the concentrate was composed of corn, soybean meal and urea. Apparent digestibility of organic matter and crude protein showed a linear association with concentrate proportion (p=0.01), but the increased concentrate levels did not affect the digestibility of fibre. The lowest ruminal pH-values were observed in animals fed with Diet 80, remaining below pH 6.0 from 6h after feeding, while in the other diets, the ruminal pH was below 6.0 not before 12h after feeding. After feeding Diet 80, the ammonia concentration in the rumen was significantly the highest. Higher dietary concentrate levels resulted in a linear increase of propionic acid concentrations, a linear reduction of the ratio acetic acid to propionic acid (p<0.01) and a linear increased synthesis of microbial nitrogen (p<0.001). The predicted production of methane was lower in diets with greater amounts of concentrate (p=0.032). The population of methanogens, R. flavefaciens and R. albus decreased with higher concentrate levels, while the population of S. ruminantium increased (p<0.05). The results indicate that greater amounts of concentrate do not decrease ruminal pH-values as much as expected and inhibit some cellulolytic bacteria without impairing the dry matter intake and fibre digestibility in Nellore steers.
Keywords: Bacteria; digestibility; fibre content; protozoa; rumen fermentation; steers; volatile fatty acids